2016
DOI: 10.1063/1.4940687
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the critical micelle concentration in simulations of surfactant systems

Abstract: Alternative methods for determining the critical micelle concentration (cmc) are investigated using canonical and grand canonical Monte Carlo simulations of a lattice surfactant model. A common measure of the cmc is the "free" (unassociated) surfactant concentration in the presence of micellar aggregates. Many prior simulations of micellizing systems have observed a decrease in the free surfactant concentration with overall surfactant loading for both ionic and nonionic surfactants, contrary to theoretical exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 67 publications
0
48
0
Order By: Relevance
“…Cationic surfactants are, in general, more expensive than anionic surfactants because of the high-pressure hydrogenation reaction required during their synthesis, yet they are often of great commercial importance, such as in corrosion inhibition [11].For ionic surfactants, it is now widely accepted that there are significant changes in the free surfactant concentrations the total surfactant loading is increased above the critical micelle concentration. This is confirmed by experiments [12][13][14], simulations [15][16][17] and theory [18][19][20].The magnitude of the decrease in free surfactant concentration for nonionic surfactants is significantly smaller than that for ionic surfactants and still somewhat controversial [21]. Depending on the nature of the hydrophilic group, synthetic surfactants are classified in four types.…”
Section: Introductionmentioning
confidence: 57%
“…Cationic surfactants are, in general, more expensive than anionic surfactants because of the high-pressure hydrogenation reaction required during their synthesis, yet they are often of great commercial importance, such as in corrosion inhibition [11].For ionic surfactants, it is now widely accepted that there are significant changes in the free surfactant concentrations the total surfactant loading is increased above the critical micelle concentration. This is confirmed by experiments [12][13][14], simulations [15][16][17] and theory [18][19][20].The magnitude of the decrease in free surfactant concentration for nonionic surfactants is significantly smaller than that for ionic surfactants and still somewhat controversial [21]. Depending on the nature of the hydrophilic group, synthetic surfactants are classified in four types.…”
Section: Introductionmentioning
confidence: 57%
“…To calculate the critical micelle concentration (CMC) we implemented the approach proposed by Santos et al, 27 who demonstrated that the CMC can be estimated by the constant value of the volume fraction free surfactant (φ oligomer ) in the accessible volume of aqueous phase (water beads in our case) when the total surfactant volume fraction in water (φ)…”
Section: Computational Detailsmentioning
confidence: 99%
“…Nonetheless, the idealized behavior of micellization ( as a function of surfactant concentration. 19 One may also look for changes in the partial molar volume of the surfactant in isobaric (constant particle number, pressure and temperature) simulations as one increases the total surfactant concentration from below to above the CMC.…”
Section: Simulation Observablesmentioning
confidence: 99%
“…One may perform linear fits of the submicellar concentration as a function of the total surfactant concentration above and below an estimate of the CMC and detect a crossing point. With any of these approaches based on submicellar concentration, even the computation of this concentration may not be straightforward.Santos and Panagiotopolous (2016) have shown that in computing the submicellar concentration as a surrogate for the CMC, one must correct the volume considered to be accessible to the free surfactant by a factor somewhat more than one would expect based on the space occupied by the micellar material 19. The idealized micelle behavior also suggests one may perform a linear fit of the total number of micelles as a function of total surfactant concentration and extrapolate this fit to find the zero intercept, representing the highest total surfactant concentration where no micelles are seen.…”
mentioning
confidence: 99%